2022
DOI: 10.3390/covid2030022
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 First Wave on Psychological and Psychosocial Dimensions: A Systematic Review

Abstract: A systematic review of the literature investigating the effects of the COVID-19 pandemic on psychological and psychosocial factors was completed. Published literature was examined using electronic databases to search psychosocial factors such as beliefs and media persuasion, social support, coping, risk perception, and compliance and social distancing; and psychological factors as anxiety, stress, depression, and other consequences of COVID-19 that impacted mental health among the pandemic. A total of 294 pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 410 publications
1
28
1
Order By: Relevance
“…Importantly, past behavior, health knowledge, intention, and planning also remained with their main effects on behavior independently of country underlining their generic importance: Only if individuals know why and how to perform physical distancing, and if they have performed this before and intend to repeat it, then they are more likely to also adopt and maintain this behavior. This finding is partially in line with a recent review study [ 53 ], which indicated that the population who were more likely to comply with social distancing included those who had high levels of knowledge about social distancing and had high intention level to perform it. In contrast, self-efficacy needs to be addressed in a country-specific manner: while in China, more motivational self-efficacy is imperative for more preventive physical distancing, in Germany more volitional self-efficacy seems to be required.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, past behavior, health knowledge, intention, and planning also remained with their main effects on behavior independently of country underlining their generic importance: Only if individuals know why and how to perform physical distancing, and if they have performed this before and intend to repeat it, then they are more likely to also adopt and maintain this behavior. This finding is partially in line with a recent review study [ 53 ], which indicated that the population who were more likely to comply with social distancing included those who had high levels of knowledge about social distancing and had high intention level to perform it. In contrast, self-efficacy needs to be addressed in a country-specific manner: while in China, more motivational self-efficacy is imperative for more preventive physical distancing, in Germany more volitional self-efficacy seems to be required.…”
Section: Discussionsupporting
confidence: 90%
“…Fear of COVID-19 infection was recognized as the prominent reason for accepting restrictions [ 22 ], but it cannot account for our result because fear often lead to anxiety symptoms. Nonetheless, adherence to COVID-19 restrictions is dependent on the extent these restrictions are perceived as effective [ 24 ] and positive attitudes such as self-efficacy and promoting one’s own health could explain the endorsement of restrictions by individuals with sustained resilience. If confirmed in specific future studies, this finding could suggest implementation of pro-adherence interventions based more on information about the benefits of containment measures than on fear of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ICTs and more generally of the Internet in emergency scenarios like the pandemic is far from being fully understood. Indeed, the web can offer not only young adults and students an opportunity to cultivate their general sense of belonging but also to receive social support [ 81 , 82 ], which could lead to better adaptation to emergency situations [ 83 , 84 , 85 ]. Future research should also clarify how loneliness varies in remote learning and blended learning conditions outside the current pandemic.…”
Section: Discussionmentioning
confidence: 99%